2019
DOI: 10.1002/jsfa.9714
|View full text |Cite
|
Sign up to set email alerts
|

Reducing the carbon footprint per unit of economic benefit is a new method to accomplish low‐carbon agriculture. A case study: adjustment of the planting structure in Zhangbei County, China

Abstract: BACKGROUND The development of low‐carbon agriculture is promising for mitigating climate change. This study used adjustments to the planting structure in Zhangbei County, China, as an example to evaluate whether the carbon footprint per unit of economic benefit is a suitable indicator of low‐carbon agriculture and to determine if low‐carbon agriculture is not necessarily low‐input non‐intensive agriculture. RESULTS The results showed that total greenhouse gas emissions increased; therefore, the adjustments to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…The conclusion of the research on the level of GHG emissions and food production is that the lowest possible emission rate per unit of output should be pursued [24]. In the literature, this indicator is called emission intensity or carbon intensity; it is related to the concept of carbon footprint, which in its general form assumes that the carbon footprint is a certain amount of GHG emissions that are considered to be related to an activity, for example, production [25].…”
Section: Introductionmentioning
confidence: 99%
“…The conclusion of the research on the level of GHG emissions and food production is that the lowest possible emission rate per unit of output should be pursued [24]. In the literature, this indicator is called emission intensity or carbon intensity; it is related to the concept of carbon footprint, which in its general form assumes that the carbon footprint is a certain amount of GHG emissions that are considered to be related to an activity, for example, production [25].…”
Section: Introductionmentioning
confidence: 99%
“…However, when changes in nitrogen emissions were calculated to assess the ecological benefits, NF a , NF y , NF v , and NF e in the CFO system were higher than those in the CWF system, while NF decreased with reduced nitrogen fertilizer application rates. These results indicated that the ecological benefits of the different farming measures might vary under different ecological objectives (Wang et al 2019).…”
Section: The Effects Of the Cropping System And Nitrogen Application Rate On The Ecological And Economic Benefitsmentioning
confidence: 92%
“…The CF values were estimated based on the LCA method, which involved the following equations (Gan., 2012;Wang et al 2019;Yang et al 2014): where CF a , CF y , CF v , and CF e represent the CF of cotton production per unit of sown area (kg CO 2 eq ha −1 ), cotton yield (kg CO 2 eq kg −1 ), production value (kg CO 2 eq CNY −1 ), and economic benefit (kg CO 2 eq CNY −1 ) per year, respectively; AI i represents the agricultural inputs applied during cotton production, which are presented in Table 1; EF i represents the GHG emission factor of each agricultural input, which are presented in Table 2; ΔC represents the GHG emissions from the change in SOC in the field soil; and yield, production value, and economic benefit are the respective seed cotton yield (kg ha −1 ), production value (CNY ha −1 ), and economic benefit (CNY ha −1 ) of cotton production each year. The values for the yield, production value, and economic benefit in this study are presented in Table S1.…”
Section: The Cf Calculationmentioning
confidence: 99%
“…Carbon emission intensity refers to the amount of carbon emissions per unit of agricultural output value or per unit of planting area, reflecting the costs and eco-efficiency of agricultural production systems [36]. According to [37][38][39], we chose carbon emissions per unit of planting area and carbon emissions per unit of agricultural output value to quantify the carbon emission intensity of the inputs of agricultural production in China, respectively. The formula is as follows:…”
Section: Calculating Carbon Emission Intensitymentioning
confidence: 99%